Designing a Facebook Interface for Senior Users. (2nd February 2014) - Gomes, Gonçalo; Duarte, Carlos; Coelho, José; Matos, Eduardo
Abstract : The adoption of social networks by older adults has increased in recent years. However, many still cannot make use of social networks as these are simply not adapted to them. Through a series of direct observations, interviews, and focus groups, we identified recommendations for the design of social networks targeting seniors. Based on these, we developed a prototype for tablet devices, supporting sharing and viewing Facebook content. We then conducted a user study comparing our prototype with Facebook's native mobile application. We have found that Facebook's native application does not meet senior users concerns, like privacy and family focus, while our prototype, designed in accordance with the collected recommendations, supported relevant use cases in a usable and accessible manner.